CONCEPTION OF ECOLOGY AS THE SUBJECT OF PROGRESSIVE LAW AND THE EMBODIMENT OF INTER-GENERATION JUSTICE - Vincentius Patria Setyawan (Faculty of Law Atma Jaya Yogyakarta University, 2024)
The unfinished discussion regarding progressive law is the subject of progressive law. Progressive law pays attention to the human aspects of judging and providing protection for entities that are